Variables that impact HPV test accuracy during vaginal self collection workflow for cervical cancer screening - Laurence Vaughan; Devin Gary; Millie Shah; Lyndsay Lewellen; Laura Galbraith; Valentin Parvu (Elsevier, 2024)
Vaginal self collection (SC) is safe and effective for human papillomavirus (HPV) testing and can increase cervical cancer screening coverage for underserved women. To better understand the impact of SC methodology on HPV test outcomes, empirical testing was conducted using different swab collection workflows. Deposition of the collection swab into resuspension buffer resulted in a 2.4-cycle reduction in threshold detection of human beta-hemoglobin during PCR when compared to "swirl-and-toss". In addition, reducing the swab resuspension volume from 10 mL to 3 mL resulted in a 2.6-cycle reduction in threshold detection of human beta-globin. A systematic literature search (01/01/2020 to 08/02/2023) of Ovid Medline and Embase, followed by data extraction and analysis, was conducted to further assess the impact of resuspension volume on performance following SC. HPV test performance for SC, relative to clinician collection (CC), was calculated for detection of cervical pre-cancer. Data were stratified by the resuspension volume ratio of SC to CC being either ≥ 1.0 or < 1.0. SC with a volume ratio of ≥ 1.0 and < 1.0 had a relative ≥ CIN2 sensitivity of 92.0 % (95 % CI: 88.0, 96.0) and 97.0 % (95 % CI: 94.0, 100), respectively. Taken together, these results suggest that SC conditions can be modified to optimize sample recovery and performance, as part of cervical cancer screening.